(untitled) (Bangladesh Journal of Agricultural Research, 2013)
This paper presents the drying kinetics of ginger rhizome under blanched and nonblanched conditions using hybrid solar dryer and mechanical tray dryer at three temperature levels. The drying rate increases with the increase in drying air temperature and blanching also increases the drying rate. The drying rate depends on shape and size of the ginger rhizomes. The highest drying rate was found for sliced samples of ginger rhizome followed by splitted and whole root samples. Five thin layer drying models were fitted to the experimental data of blanched and sliced ginger rhizomes. The Page equation was found to be the best to predict the moisture content of sliced ginger rhizome in thin layer. The agreement between the predicted and experimental results was excellent. Colour of ginger rhizomes was slightly changed after drying. Lightness of ginger rhizomes decreased with an increase in drying temperature for all samples except sliced and blanched samples. For drying of ginger rhizome, it should be sliced and blanched and dried below 70°C for better quality dried products. Bangladesh J. Agril. Res. 38(2): 301-319, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15892